Peran Bahasa Daerah dalam Pelestarian Warisan Budaya Nusantara - Ningrum Amalia Putri (Lembaga Penelitian dan Pendidikan (LPP) Kalibra, 2025)
Background: Regional languages across the Indonesian archipelago embody rich cultural knowledge and heritage, serving as living repositories of local traditions, values, and expressions. However, globalization and the dominance of national and global languages often marginalize these linguistic treasures, risking cultural erosion. Purpose: This paper aims to investigate how the integration of regional languages in educational settings—through a sociolinguistic approach—can bolster communicative competence while fostering cultural preservation. Specifically, it explores how regional language instruction enriches students’ grasp of variation, register, politeness, and pragmatic adaptation. Methods: Employing a descriptive qualitative design through literature review, the study involves systematic document analysis of academic sources—journal articles, books, and proceedings indexed in databases such as Google Scholar. Data collection targets theoretical frameworks, empirical findings, and pedagogical models pertaining to sociolinguistic language instruction, diverse linguistic registers, and pragmatic competence. Thematic content analysis is applied to identify recurring patterns, concepts, and insights. Key Findings: Implementation strategies include authentic discourse analysis, role-play simulations, and discussions around language variation in both formal and informal contexts. These methods enhance students’ understanding of linguistic variation, register sensitivity, and context-appropriate usage. They further promote pragmatic and sociocultural competence, empowering students to adjust their language use across different social situations. Conclusion: Sociolinguistic instruction serves as a vital bridge between linguistic knowledge and real-world communicative practice. Embedding regional languages into language education not only supports cultural continuity but also equips learners with the skills required for effective, context-sensitive communication in today’s diverse interactional landscape.